THE EFFECT OF WATER QUALITY AND NUTRIENT ACCUMULATION ON RICE GROWTH IN INTEGRATED AQUACULTURE-AGRICULTURE - ABRAHAM, O. V; AKINWOLE, A. O; ADENIYI, A. O; ABDULLAHI, U. U; AKPOBOME, S. O. (Nigerian Journal of Fisheries, 2020)
This experiment was conducted to evaluate the effect of Water Quality on rice growth performance in an integrated aquaculture-agriculture surrounded by a trench which serves as culture for fish. Oryza sativa (FARO 49) was planted in nursery bed and transplanting was done after 15 days at a spacing of 10cm by 10cm. Rice growths were accessed by measuring morphometric variables: plant height and leaves as well as reproductive stage: yield throughout productive period. Pond water quality and sediment nutrient accumulation were monitored. Rice plant height measured after sixteen weeks was 146.98±11.65cm and yield recorded was 2666.7kg/ha. Water quality parameters such as pH, temperature, dissolved oxygen, NO3-N, NO2-N and NH3were within recommended range; showed a significant difference through improved physical-chemical parameters and revealed NO3-N, NO2-N and NH3 are strongly correlated positively and significant to rice growth. There was significant different (p> 0.05) during production between rice plant and nitrogen content present in soil. Sediment accumulated showed high nutrient received and manure with supplementary feed. The results showed that patterns of pond water and nutrient flows were strongly influenced by fish farming activities. Hence, integrating fish pond with crop has strengthened nutrient recycling which enhanced better farm outputs and safeguard the environment.